Effects of gender, age and menopausal status on serum apolipoprotein concentrations. (29th April 2016) - Anagnostis, Panagiotis; Stevenson, John C.; Crook, David; Johnston, Desmond G.; Godsland, Ian F.
Summary: Objective: To undertake a comprehensive evaluation of apolipoprotein risk markers for cardiovascular disease (CVD) according to gender, age and menopausal status. Design: Cross‐sectional analysis of independent associations of gender, age and menopause with serum apolipoproteins. Participants: Apparently healthy Caucasian premenopausal ( n = 109) and postmenopausal ( n = 252) women not taking oral contraceptives or hormone replacement, and Caucasian men ( n = 307). Measurements: Serum apolipoprotein (apo) B, A‐I and A‐II concentrations were measured, plus serum total cholesterol, low‐density and high‐density lipoprotein cholesterol (LDL‐C and HDL‐C, respectively), triglycerides, cholesterol in HDL subfractions and the apoB/apoA‐I, LDL‐C/apoB, HDL‐C/apoA‐I and HDL‐C/apoA‐II ratios. Analyses were undertaken with and without standardization for confounding characteristics and in 5‐year age ranges. Results: Overall, apoB concentrations were highest in men but in women rose with age and menopause to converge, in the age range of 50–55 years, with concentrations in men. The LDL‐C/apoB ratio was generally higher in women than in men. ApoA‐I concentrations were highest in postmenopausal women and lowest in men (standardized median (IQR) 144 (130, 158) vs 119 (108, 132) g/l, respectively, P < 0·001). ApoA‐II concentrations were also highest in postmenopausal women but were lowest in premenopausal women (40·3 (37·5, 44·5) vs 32·9 (30·5, 35·7) g/l, respectively, P < 0·001). Nevertheless, postmenopausal women had HDL‐C/apoA‐I and HDL‐C/apoA‐II ratios approaching the lowest ratios, which were seen in men. Conclusions: Consistent with adverse effects on CVD risk, male gender, ageing in women and menopause were associated with increased apoB concentrations, and menopause and male gender were associated with a decreased cholesterol content of HDL particles.